Preliminary taxonomic review of the genus Coptotriche Walsingham, 1890 (Lepidoptera: Tischeriidae) in China, including descriptions of three new species - Zhang, Xiuying; Sun, Hao; Li, Houhun (Zootaxa, 2025)
Eight species of the genus Coptotriche Walsingham, 1890 are reported from China. Three species are described as new: C. basilata sp. nov., C. basicurvata sp. nov. and C. brevissima sp. nov. One species, C. minuta Diškus & Stonis, 2014, is recorded for the first time in China. Images of adults and genitalia of the new and newly recorded species are given, along with a key to the eight Coptotriche species distributed China.